THE INFLUENCE OF ACADEMIC SERVICE QUALITY ON STUDENT SATISFACTION MEDIATED BY TUITION FEES AT THE POSTGRADUATE PROGRAM OF TADULAKO UNIVERSITY IN PALU CITY - Syaiful, Muhamad; Bachri, Syamsul; Parani, Syamsul Bahri Dg. (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2025)
This study means to look at and dissect the impact of scholastic assistance quality on understudy fulfillment interceded by educational expenses at the Tadulako College Postgraduate program in Palu City. Questionnaires were distributed to students for data collection. The participants in this study were master's and doctoral students enrolled in Tadulako University's Postgraduate Program in Palu City during the 2023–2024 academic year. The inspecting method utilized likelihood examining. deciding the quantity of tests utilizing the slovin equation and got an example of 100 individuals as respondents. Using Smart-PLS 4.0 software, the measurement model (outer model) and structural model (inner model) are evaluated as part of the data analysis technique, which makes use of descriptive statistical analysis and partial least square (PLS) analysis. The outcomes showed that the nature of scholarly administrations affected understudy fulfillment, getting a way coefficient worth of 0.483 and a P-worth of 0.000. The immediate impact of scholastic help quality on educational expenses has a way coefficient worth of 0.564 and a P-worth of 0.000. The path coefficient and the P-value for the direct effect of tuition fees on student satisfaction were 0.366 and 0.000, respectively. The academic service quality variable has a path coefficient value of 0.207, a P-value of 0.00, and an upsilon v value of 0.898, all of which indicate that tuition fees have a significant indirect impact on student satisfaction.